The Eocene sea urchins from Plače near Ajdovščina, Western Slovenia - Mikuž, Vasja (Geologija, 2007)
Considered are Eocene sea urchins from Plače near Ajdovščina. Nine specimens were found and eight distinct genera determined: Conoclypus, Echinolampas, Rhyncholampas, Ditremaster, Schizaster, Linthia, Cyclaster and Macropneustes. The species of listed genera indicate Middle Eocene - Lutetian age of beds. The sea urchin assemblage is of mixed character, recorded were forms typical for shallow environments, and others typical for deeper marine environments. The entire assemblage from Plače is comparable with Eocene assemblages of sea urchins of the Tethys sedimentation region.